2022
DOI: 10.1002/ps.6875
|View full text |Cite
|
Sign up to set email alerts
|

Spray performance evaluation of a six‐rotor unmanned aerial vehicle sprayer for pesticide application using an orchard operation mode in apple orchards

Abstract: BACKGROUND: In the last decade, unmanned aerial vehicle (UAV) sprayers have been growing rapidly worldwide as a new method for pesticide application, especially in Asian countries. More and more manufacturers and service providers are currently aiming at UAV spraying operation for fruit trees with higher economic value. We evaluated the spray performance of an electric six-rotor UAV sprayer using an orchard operation mode (different application volumes and flight patterns) in a hilly apple orchard with small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…This result indicated that UAV application technology is unstable, which could affect the overall pest control in the orchards. Generally, it could achieve pest control effects when the deposit coverage exceeds 1% during UAV application ( Wang et al, 2022 ) due to its high-concentration spraying property. The results indicated that UAV application could adapt to orchard pest control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicated that UAV application technology is unstable, which could affect the overall pest control in the orchards. Generally, it could achieve pest control effects when the deposit coverage exceeds 1% during UAV application ( Wang et al, 2022 ) due to its high-concentration spraying property. The results indicated that UAV application could adapt to orchard pest control.…”
Section: Resultsmentioning
confidence: 99%
“…The former method has been recognized as a high-efficiency pesticide application technology and is widely used for pest control in orchards ( Li et al, 2022 ). However, it is only suitable in standardized orchards with fixed wide spacing and relatively flat pavement ( Wang et al, 2022 ). Human spray guns can make up for this shortcoming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spraying with UASS has proven to be feasible in the prevention and control of crop diseases and pests by spraying insecticides or fungicides ( Meng et al, 2018 ; Yan et al, 2022 ). In the case of trees grown on steep slopes, the quality of the application is partially limited by the flight altitude of the sensor and terrain following technology with the help of lidar for example ( Meng et al, 2022b ; Wang C. et al, 2022 ). Moreover, a denser crop canopy also presents limitations in terms of droplet penetration ( Chen et al, 2020b ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring an automatic sprayer with a high degree of automation and a high pesticide utilization is a hot spot for agricultural machinists. There are mainly two thorny problems in the development of automated orchard sprayers: one is to achieve efficient penetration of pesticides in a low dense canopy and reduce the loss of chemical solution ( Meng et al, 2022 ; Wang C. et al, 2022 ), while the other is to let the machine traverse the orchard autonomously without manual control in the orchard with a closed canopy and blocked vision ( Bergerman et al, 2015 ; Ye et al, 2018 ; Zhang et al, 2020 ). Considerable research has been conducted on the above two issues.…”
Section: Introductionmentioning
confidence: 99%